Concrete Structures Life Span Based on Carbonation Rate Using Artificial Neural Network - MF Nuruddin; ABM Diah; TR Biyanto; M Sigit Darmawan; Ridho Bayuaji (Jurnal Aplikasi Teknik Sipil, 2011)
The study on the influence of carbonation on concrete is critical as it affects the life span of the concrete structure when corrosion of reinforcement takes place. This research elucidates the carbonation effect on concrete from different environments and concrete samples of grades 15, 20, 25, 30, 35, 40, and 50 MPa. Two set of samples were considered namely controlled sample in the laboratory and on sites samples. In conclusion, it was found that across the board on average, carbonation improved the concrete integrity by 11%. The development of the model using neural networks for the prediction of a carbonation penetration, which consists of two input variables and one output variable were presented.